Initiation and evolution of fault‐controlled slope‐parallel submarine channels: Miocene eastern slope of Yinggehai Basin, South China Sea. (26th October 2022) - Wang, Zhen; Xian, Benzhong; Liu, Jingyan; Khan, Majid; Fan, Caiwei; Li, Hui; Wang, Junhui; Zhang, Ximeng; Liu, Jianping; Chen, Peng; Wu, Qianran; Zhang, Wenmiao
Abstract: Submarine channels act as the main conduits for the transport of sediment to deep‐water basins by sediment gravity flows. The interplay between fault‐related deformation and the initiation and development of the channels is poorly known. Here, we present the identification, formation and evolution of the Miocene slope‐parallel channel by employing 3D seismic reflection, wireline‐log and core data in the eastern slope of Yinggehai Basin, South China Sea. Based on the lengths and plan‐view shapes, a total of three different types of fault‐associated slope‐parallel depressions have been identified. The depressions were formed in the fault zone and controlled by the reactivation of the underlying older faults. Among them, Type‐1 depressions are short (<20 km) oval or circle shaped possessing only one depocenter. Type‐2 depressions are elongated (25–70 km), and usually have multiple depocenters. Type‐3 depressions, which are usually connected by slope‐perpendicular channels in the head and middle, are longer (more than 190 km) and connect shallow and deep‐water basins. The analysis of morphology, erosivity and material transport shows that Type‐3 depressions are fully fledged channels. Type‐1 and Type‐2 depressions are channel precursors representing the initial stage of channel evolution. With this motive, a model for the initiation and evolution of slope‐parallel submarine channels controlled by strike‐slip‐extensional faults is presented. Unlike the previous investigations which suggest that erosion takes place at the inception of submarine channel formation, the fault‐controlled slope‐parallel channel is mainly controlled by faulting and has no initial erosive base and does not develop levees. The depressions are extended and elongated by the continuous fault activity. It was not until the slope‐parallel depression connected with large‐scale slope‐perpendicular channels transporting materials into the depression via erosive turbidity currents that it evolved into a channel‐levee system. This study is of global importance for understanding submarine channel generation and evolution since the fault‐controlled slope‐parallel channels have been found in tectonic active basins worldwide. Abstract : Schematic diagram showing the formation and evolution steps of the fault‐controlled slope‐parallel submarine channel.